Máscaras de Ezra Pound em Personae (1909): uma tradução comentada - Delgado Filho, Guilherme de Oliveira (2020)
A poet of undeniable importance for modern English poetry, the American Ezra Pound (1885- 1972) is the great motivation of this work. His third book of poems, Personae, from 1909, is understood here as a paradigmatic title for systematically bringing together the formulation of the so-called “poundian masks”: masks by which Pound appropriated the personae of poets of the past through a complex exercise in the adoption of technique, voice or characteristics of these same authors in order to revive and re-present traditions that he considered important, but also to shape a personal language, as pointed out by Brooker (1979). Our general objectives were to collaborate so that the translation and reception of the author in the Brazilian context approach its multiple facets, attenuating the lapse that is still observed in his poetic work, and highlight the importance of this particular period for the unfolding of his later work. Our specific objective was to carry out a commented translation of a precedent note and also six poems from Personae (1909) centered on three fundamental authors for Ezra Pound’s first poetry: Robert Browning (1812-1889), François Villon (1431 - after 1463) and William Butler Yeats (1865-1939). Our translation sought to comment not only on the dialogue that Pound maintained with these poets – and the particular way in which he absorbed them in his poetry –, but also the means we used to respond to the expectations of our theoretical frame, which was valued for relativizing extremes and assuming a practical perspective of translation based on reflections by Britto (2012) and Flores (2014). In the midst of the analysis process, we used Campos, H. (2015 [2013]), Meschonnic (2010), Spina (2003 [1971]) and especially Britto (2006) to highlight possible formal and functional correspondences between original and translation and reflect on the possibilities of recreating them successfully. Our results point to the relevance of a broader discussion on the historicity of traditional poetic forms, to the importance of form for the young Ezra Pound and to a revaluation of his first poetry.